2012
DOI: 10.3923/pjbs.2012.804.812
|View full text |Cite
|
Sign up to set email alerts
|

Textile Effluent Induced Genotoxic Effects and Oxidative Stress in Clarias gariepinus

Abstract: Human and ecological disorder experienced in industrial settlements as a result of improper disposal of chemicals such as textile effluent calls for careful surveillance on the state of the environment. This study investigated the toxicity of textile effluent discharge using biochemical and cytogenetic responses to ascertain the acute and sub lethal effects on Clarias gariepinus. The 96 h LC50 of C. gariepinus exposed to the textile effluent was 8.203 ml L(-1). Fourteen day exposures to 1, 2, 4 and 6 ml L(-1) … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
5
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(8 citation statements)
references
References 10 publications
3
5
0
Order By: Relevance
“…Studies are scarce on the cytotoxicity and genotoxicity of abattoir effluents in both terrestrial and aquatic organisms, but there are similar observations as obtained herein with other wastewater/effluents from Nigeria [8][9][10]. Arsenate observed at higher concentrations in the tested abattoir effluent has been reported to possess clastogenic and aneugenic properties which may increase genomic instability enhancing mutagenesis and carcinogenesis in biological systems [22,23].…”
Section: Discussionsupporting
confidence: 69%
See 1 more Smart Citation
“…Studies are scarce on the cytotoxicity and genotoxicity of abattoir effluents in both terrestrial and aquatic organisms, but there are similar observations as obtained herein with other wastewater/effluents from Nigeria [8][9][10]. Arsenate observed at higher concentrations in the tested abattoir effluent has been reported to possess clastogenic and aneugenic properties which may increase genomic instability enhancing mutagenesis and carcinogenesis in biological systems [22,23].…”
Section: Discussionsupporting
confidence: 69%
“…Its use in previous studies to assess the cytogenotoxic effects of municipal landfill leachate [8], e-waste leachates, and e-waste contaminated underground water [9] and textile effluent [10] using micronucleus test suggests its sensitivity to detecting the DNA damaging effects induced by mixture of xenobiotics in the effluents. The ease to culture C. gariepinus due to rapid turnover rate and high adaptation to varying laboratory conditions accounts for its use in scientific studies and as the most locally consumed African clarrid in Nigeria.…”
Section: Introductionmentioning
confidence: 99%
“…Behavioural changes, including restlessness, erratic swimming and surfacing, recorded in the present study may be an avoidance syndrome developed by fish in reaction to the fertiliser toxicity. The behavioural changes reported in this investigation compare favourably with the observations of Dube and Hosetti (2010), Ayoola et al (2012) and Aziz et al (2014), who exposed various species of fish to different toxicants.…”
Section: Discussionsupporting
confidence: 89%
“…The genotoxicity was revealed by Poongothai et al [18] in five fishes from sewage polluted water; Ayllon et al [2] in Salmo trutta from River Trubia (heavy metals pollutants added from old military factory); Cavas and Ergene-Gozukara [5] in Oreochromis niloticus exposed to petroleum refinery and chromium processing plant effluents and Matsumoto et al [16] due to tannery effluent in Oreochromis niloticus. Similarly, micronuclei formation in fishes from polluted water bodies have also been reported by Ergene et al [8] in Clarias gariepinus, Mugil cephalus and Alburnus orontis from polluted sites of Goksu delta (Turkey); Kirschbaum et al [13] in Centropomus parallelus from highly polluted estuary, Choudary et al [12] observed similar finding like induction of Micronuclei in fish Erythrocyte with one micronucleus, e, f Erythrocyte with two micronuclei, g, h Erythrocyte with three to five micronuclei Channa punctatus exposed to chromium trioxide, Ayoola et al [3] observed MN in fish Clarias gariepinus exposed to textile effluent and Saleh [21] in Cyprinus carpio from polluted water lake, Uluabat. Numerous studies have shown that fishes after exposure to different heavy metals under both laboratory and conditions revealed high frequency of micronuclei and nuclear abnormalities [1,19].…”
Section: Discussionsupporting
confidence: 64%